2012
DOI: 10.1177/1069397112450851
|View full text |Cite
|
Sign up to set email alerts
|

Parental Nurturance in the Standard Cross-Cultural Sample

Abstract: In recent years attachment theory has matured into a wide-ranging conceptual framework with sufficient power to explain important features of individual and social variability across societies. In the research reported here, the empirical work directed by attachment theory is used to expand existing codes to measure more fully those aspects of parent-child interaction that facilitate or retard the child’s development. This article presents the coding system and scores on parental nurturance for each of the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…found that great grandparent involvement was associated with better social skills and less emotional or behaviour problems of adolescent, especially in the lone-parent and step-families [29, 30]. Meanwhile, according to the attachment theory [3032], that the construction of secure attachment relationship with alternate caregivers can be the foundational support for children’s development of mental health [33]. It was possible that they were well taken care of by alternate caregivers (mostly were grandparents) [29] when they were separating from one or two parents.…”
Section: Discussionmentioning
confidence: 99%
“…found that great grandparent involvement was associated with better social skills and less emotional or behaviour problems of adolescent, especially in the lone-parent and step-families [29, 30]. Meanwhile, according to the attachment theory [3032], that the construction of secure attachment relationship with alternate caregivers can be the foundational support for children’s development of mental health [33]. It was possible that they were well taken care of by alternate caregivers (mostly were grandparents) [29] when they were separating from one or two parents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considering the complex process of child development and the effects of these confounding factors, the present study tried to make them controlled as far as possible in analysis. Another explanation is that, according to the attachment theory, the child who has a stable relationship with a primary caregiver (anyone who provides the child most of the care and related social interaction) are more prone to secure attachment [26] which can support the development of their cognitive skills, emotional [27] and social competence [28]. Studies also found that a good relationship with grandparents can help children reduce the risk of depression [29].…”
Section: Discussionmentioning
confidence: 99%
“…Infants cannot exit unpredictable or insensitive care giving relationships. Instead they must manage themselves as best they can within such relationships (8) . Secure attachment is when children feel secure in the presence of their caregivers.…”
Section: Introductionmentioning
confidence: 99%